Syntactic Categories in Tukang Besi - Donohue, Mark (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1999)
ABSTRACTExamining syntactic categories in Tukang Besi, an Austronesian language of Indonesia, we find that there are additions to the traditional fixed categories. As well as the firmly definable categories of nouns and verbs, there are many lexical items that are precategorial: they may be used, without derivation, with either nominal morphosyntax or verbal morphosyntax. Additionally, there is a class of 'adjectives' that display odd behavior in terms of morphological markedness reversals and functional use, and which, under closer examination, turn out to have a variable categorial status, dependent on the structural position in which they are used, obligatorily appearing as part of the head of their phrase, V in a VP and N in an NP. Morphosyntactic tests for the different claims are given and discussed.